Bimodulus-plastic model for pre-failure analysis of fiber reinforced polymer composites - Boon, Yi Di (2019)
Fiber-reinforced polymer composites, such as carbon-epoxy composites, are found to exhibit non-linear behavior when mechanically loaded in the transverse and shear directions. Experimental studies suggest that the non-linear behavior is due to two mechanisms: (i) damage in the matrix in the form of cracks and (ii) yielding of the matrix followed by plastic deformation. In this study, a bimodulus-plastic model that includes these two different damage mechanisms to simulate the non-linearity prior to failure is proposed. The pre-failure, onset of failure and post-failure analysis with the proposed model is discussed in detail with emphasis put on the transverse and shear components. The process of determining the material properties and parameters required for defining the new model is discussed and demonstrated. The newly developed model is then validated against the experimental results from three-point flexure tests on the composites. The correlation was good showing that the proposed model was able to simulate accurately the non-linear behavior of the composites and thus predict the failure. Finally, the model is applied to a case study on the failure of a composite riser under internal pressure loads.